A review of advantages and challenges of using engineered nanoparticles for waste and wastewater treatments - Sari Erkan, H.; Bakaraki Turan, N.; Onkal Engin, G.; Bilgili, M. S. (SPRINGER, 2021)
The continuous increase in engineered nanoparticles (ENPs) usage in environmental, industrial and agricultural applications is known to be associated with their further release to the environment. Recently, the presence of nanoparticles in wastewater and sewage systems has become one of the negotiable topics taking the attention of many scientists. ENPs can be evaluated as pollutants that must be eliminated from wastewater before being discharged to the aquatic and soil environment due to their potential toxicity risks. However, the supportive role of ENPs in the wastewater treatment process is discovered recently highlighting their possible usage in different treatment methods. ENPs can offer novel opportunities for the development of new generation water treatment systems, as they enable modular and multifunctional treatment solutions. This review paper focuses mainly on the effects of ENPs' presence in wastewater and activated sludge. Besides, the paper discusses the beneficial usage and possible applications of ENPs in different treatment technologies enhancing the treatment process in detail.
Keywords: Engineered nanoparticles; Wastewaters; Activated sludge; Treatment methods; Environmental Sciences & Ecology